1997
DOI: 10.1074/jbc.272.35.21932
|View full text |Cite
|
Sign up to set email alerts
|

Active-site Arg → Lys Substitutions Alter Reaction and Substrate Specificity of Aspartate Aminotransferase

Abstract: and Arg 386 in substrate binding, the effects of their substitution on the activity toward long chain monocarboxylic (norleucine/2-oxocaproic acid) and aromatic substrates diverged. Whereas the R292K mutation did not impair the aminotransferase activity toward these substrates, the effect of the R386K substitution was similar to that on the activity toward dicarboxylic substrates. All three mutant enzymes catalyzed as side reactions the ␤-decarboxylation of L-aspartate and the racemization of amino acids at fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 36 publications
3
51
1
Order By: Relevance
“…7,8 The !220-fold decrease in the k cat of the a,c-replacement activity of eCGS-R361K is in keeping with the 55-fold decrease in this parameter reported for the corresponding AATase-R386K but contrasts with the 4-fold decrease in the k cat of CBL-R372K. 7,11,12 The observed reductions in the activity of the eCGS and eAAT variants reflects differences in the binding orientation and conformation of the substrates, such that they are not optimally positioned for catalysis. 12 In contrast, the substantially smaller decrease in the k cat of eCBL-R372K likely reflects the facile nature of the a,b-elimination of L-Cth, which, in contrast with the transamination of eAATase and a,c-replacement reaction of eCGS, does not require the generation of a ketimine intermediate or the binding of a second substrate.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…7,8 The !220-fold decrease in the k cat of the a,c-replacement activity of eCGS-R361K is in keeping with the 55-fold decrease in this parameter reported for the corresponding AATase-R386K but contrasts with the 4-fold decrease in the k cat of CBL-R372K. 7,11,12 The observed reductions in the activity of the eCGS and eAAT variants reflects differences in the binding orientation and conformation of the substrates, such that they are not optimally positioned for catalysis. 12 In contrast, the substantially smaller decrease in the k cat of eCBL-R372K likely reflects the facile nature of the a,b-elimination of L-Cth, which, in contrast with the transamination of eAATase and a,c-replacement reaction of eCGS, does not require the generation of a ketimine intermediate or the binding of a second substrate.…”
Section: Discussionmentioning
confidence: 44%
“…7,11,12 The observed reductions in the activity of the eCGS and eAAT variants reflects differences in the binding orientation and conformation of the substrates, such that they are not optimally positioned for catalysis. 12 In contrast, the substantially smaller decrease in the k cat of eCBL-R372K likely reflects the facile nature of the a,b-elimination of L-Cth, which, in contrast with the transamination of eAATase and a,c-replacement reaction of eCGS, does not require the generation of a ketimine intermediate or the binding of a second substrate. The observed 80-and 750-fold decreases in the k catR of the R106A and R48K variants are likely also the result of suboptimal positioning and conformation of L-OSHS within the active site of eCGS.…”
Section: Discussionmentioning
confidence: 99%
“…In a genomic sequence analysis, we were unable to find candidate mammalian DR genes based on homology to serine racemase or bacterial aspartate racemases, which are either PLP-independent or PLP-dependent enzymes (14,15). Vacca and coworkers (16)(17)(18) demonstrated that glutamate-oxalacetate transaminase (GOT) can generate small amounts of D-aspartate in the process of transaminating Laspartate to L-glutamate, and that formation of D-aspartate is augmented in GOT mutants, wherein histidine replaces tryptophan-140 and lysine replaces arginine-292. Tryptophan-140 normally prevents access of a proton donor, such as a water molecule, which can effectuate racemization (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A); however, replacement of tryptophan-140 by histidine allows direct protonation by histidine for racemization. In addition, transformation of arginine-292 to lysine in GOT mutants facilitates access of water molecules by possibly interfering with substrate induced closure of the enzyme's active site and enhances racemization (18).…”
Section: Resultsmentioning
confidence: 99%
“…Molecular Interaction between the Guanido Group and the Carboxyl Group-Molecular interaction between the guanido group of arginine and the carboxyl group in the substrate or the active site residues of enzyme was reported to be crucially involved in the interaction between the substrate and the enzyme (31)(32)(33)(34)(35)(36). The ionized guanido group of arginine can form a planar structure due to the sp 2 configuration of guanido carbon atom, so that a stable planar ion pair can be generated by forming a coplanar structure between the guanido group and the negatively charged carboxyl group.…”
Section: Figure 3 Stereo View Of Mae2 In Complex With Malonate or Mamentioning
confidence: 99%